Linking language and cognition in infancy. - Perszyk, Danielle R.; Waxman, Sandra R.
Human language, a signature of our species, derives its power from its links to human cognition. For centuries, scholars have been captivated by this link between language and cognition. In this article, we shift this focus. Adopting a developmental lens, we review recent evidence that sheds light on the origin and developmental unfolding of the link between language and cognition in the first year of life. This evidence, which reveals the joint contributions of infants? innate capacities and their sensitivity to experience, highlights how a precocious link between language and cognition advances infants beyond their initial perceptual and conceptual capacities. The evidence also identifies the conceptual advantages this link brings to human infants. By tracing the emergence of a language?cognition link in infancy, this article reveals a dynamic developmental cascade in infants? first year, with each developmental advance providing a foundation for subsequent advances. -- (from the author)
Keywords: Infancy; Language acquisition; Conceptual development; Categorization; Developmental plasticity; Developmental tuning